Enemy at the gates - Annaud, Jean-Jacques.; Paramount Pictures ([s.l.] Paramount Pictures, 2001)
The year is 1942 and the Nazis are cutting a deadly swath through Russia. Under the leadership of Kruscher (Bob Hoskins), the citizens of Stalingrad are mounting a brave resistance Spurred by the exploits of their local hero, Vassili Zaitsev (Jude law). An expert sniper, Vassilis deeds have become legendary - thanks to propaganda produced by Vassili's best friend, a political officer named Danilov (Joseph Fiennes). To stop Vassili, the Germans dispatch their best sniper, Major Konig (Ed Harris), to Stalingrad. When Vassili and Danilov both fall in love with a beautiful soldier (Rachel Weisz), Danilov deserts his friend, leaving Vassili to face his German counterpart alone.
VCD
Written by Alain Godard and Jean-Jacques Annaud ; John D. Schofield, produced and directed by Jean-Jacques Annaud
Jude Law, Joseph Fiennes, Rachel Weisz, Bob Hoskins and Ed Harris.
Keywords: War Films -- Russia; Feature films